(untitled) (Kohesi: Jurnal Sains dan Teknologi, 2025)
As the population grows, the need for educational facilities increases. Therefore, Widya Dharma University Pontianak (UWDP) has developed a new 10-story building with a total floor area of 4,016 m². The operation of the lecture building will inevitably involve the use of electrical energy. The primary function of electrical energy is to meet the needs of learning facilities, services, and the comfort of all building users to ensure smooth academic activities. This study employs a literature review and descriptive analytical method. During the planning process, several calculations were performed, including determining lighting requirements using DIALux Evo software, cross-sectional area of conductors, current rating of circuit breakers, and a cost estimate (RAB). Based on the calculations and analysis conducted, the number of light points required in each classroom is 16 points, with a total power of 336 Watts. The type of conductor used is NYM 2 × 2.5 mm² with a fuse rating of 4 Amperes. The total cost of the entire electrical installation work in the classrooms is IDR 45.817.000,00. From this study, it is hoped that an electrical installation plan compliant with SNI 6197 2020, PUIL 2020, and PLN standards can be developed, ensuring efficient and effective use of electrical energy in the academic building while providing comfort for building users Seiring dengan pertumbuhan penduduk maka kebutuhan akan fasilitas pendidikan semakin meningkat, oleh karena itu Universitas Widya Dharma Pontianak (UWDP) mengembangkan sarana gedung baru 10 lantai dengan total luas bangunan 4.016 m². Operasional gedung perkuliahan tidak akan terlepas dari penggunaan energi listrik. Fungsi utama energi listrik yaitu untuk memenuhi kebutuhan fasilitas belajar, pelayanan, dan kenyamanan seluruh pengguna gedung agar kegiatan perkuliahan berjalan lancar. Penelitian ini menggunakan metode studi literatur dan deskriptif analitik. Pada proses perencanaannya dilakukan beberapa perhitungan yaitu menghitung kebutuhan iluminasi penerangan menggunakan software DIALux Evo, luas penampang penghantar, rating arus pengaman, dan rencana anggaran biaya (RAB). Berdasarkan hasil perhitungan dan analisa yang telah dilakukan diperoleh jumlah titik lampu yang butuhkan pada ruang kelas sebanyak 16 titik pada masing-masing kelas dengan total daya sebesar 336 Watt. Jenis penghantar yang digunakan adalah NYM 2 × 2,5 mm2 dengan besar pengaman 4 Ampere. Biaya total seluruh pekerjaan instalasi listrik pada ruang kelas sebesar Rp. 45.817.000,00. Dari penelitian ini, diharapkan dapat menghasilkan perencanaan instalasi listrik yang sesuai dengan SNI 6197 tahun 2020, PUIL tahun 2020 dan standar PLN, sehingga penggunaan energi listrik pada gedung perkuliahan dapat berlangsung secara efisien dan efektif, serta mampu memberikan kenyamanan bagi para pengguna gedung